Calcium supplementation in young children in Asia: Prevalence, benefits and risks - Che, S.; Binns, Colin; Maycock, B. (Nova Science Publishers, Inc., 2013)
Calcium is essential for maintaining bone health in infants and young children. The calcium intakes of weaning infants and children in Asia are relatively low in comparison to their Western counterparts. This is an increasing concern for Asian parents and is one reason the Asia Pacific region is becoming a large market for vitamins and dietary supplements. However, there is a lack of data on the long-term benefits to early calcium supplementation of healthy infants and young children. The objective of this chapter is to discuss the appropriate calcium intakes for infants and young children, the risks and benefits of calcium supplementation and to review the proportion of children in Asia who are taking calcium supplements. To achieve our objective a literature review was undertaken of the English language databases PubMed and Web of Knowledge. Studies were selected that reported outcomes of calcium intake in infants and young children, as well as systematic reviews of such studies. Studies were undertaken of children in China and a comparison group of Chinese children living in Australia to document the use of calcium supplements. The prevalence of dietary supplementation among children under five years old in China (30.0%) was higher than in Australia (21.6%). In supplement users in China, 60.3% of them took calcium supplementation while only a small number in Australia (8%) took calcium supplements. Age and feeding method of the child (ever breastfed or not) were associated with nutritional supplementation in Australia, while household income and mother's educational status were significantly related to the use of dietary supplements including calcium supplements in China. More than half of the children took supplemental calcium in the form of calcium gluconate (51.8%) and the average intake from supplements was 131 mg per day. There is little evidence to support the general use of calcium supplements in infants who were exclusively breastfed or formula fed. Evidence from recent studies does not support the use of calcium supplementation in healthy children as a public health intervention. However, for weaning infants and children with low calcium intakes, increased intake of calcium-rich foods should be encouraged. If adequate calcium cannot be achieved through food sources, supplementation may be an effective alternative. More studies are required in infants and young children with low calcium intakes, particularly those living in Asian countries or children of Asian ethnic origin. © 2013 Nova Science Publishers, Inc. All rights reserved.